2011
DOI: 10.1007/s13197-011-0524-8
|View full text |Cite
|
Sign up to set email alerts
|

Sensory characterization of doda burfi (Indian milk cake) using Principal Component Analysis

Abstract: Traditional sweetmeats of various countries hold a great and promising scope in their improvement and in order to tap the potential of the same, several companies and cooperative federations have started their organized production. Doda burfi, a heat desiccated and popular sweetmeat of northern India, is one of the regional specific, unfamiliarized products of India. The typical sweetmeat is characterized by caramelized and nutty flavour and granular texture. The purpose of this study was to determine the clos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 14 publications
1
20
0
Order By: Relevance
“…The QDA GPA and FP GPA results both indicate that P3 and P4 were similar according to their narrow location but were different from P7 and P8 because of the long distance on the plots . Furthermore, although the total explained variance of the FP GPA plot was less than that of the QDA plot, both methods described the same characteristics of these products, indicating that FP is as efficient as QDA when characterizing and discriminating among the red sufu products.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…The QDA GPA and FP GPA results both indicate that P3 and P4 were similar according to their narrow location but were different from P7 and P8 because of the long distance on the plots . Furthermore, although the total explained variance of the FP GPA plot was less than that of the QDA plot, both methods described the same characteristics of these products, indicating that FP is as efficient as QDA when characterizing and discriminating among the red sufu products.…”
Section: Resultsmentioning
confidence: 86%
“…The QDA GPA and FP GPA results both indicate that P3 and P4 were similar according to their narrow location but were different from P7 and P8 because of the long distance on the plots. 45 Furthermore, although the total explained variance of the FP GPA plot was less than that of the QDA plot, both methods described the same characteristics of these products, indicating that FP is as efficient as QDA when characterizing and discriminating among the red sufu products. Delarue and Sieffermann 10 also concluded that the two profiling methods were similar regarding the structure of the product space, and many of the same descriptive characteristics were obtained using the QDA and FP methods with fruit dairy products.…”
Section: Comparison Of Sensory Mapsmentioning
confidence: 91%
“…The plot shows that ten ice cream samples were separated into four quadrants with different distances. In a PCA observation score plot, the shorter the distance between two products, the higher their degree of similarity (Chawla et al ., ). Distances between A1, A2 and A3 were the nearest, suggesting that they were the most similar products (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Sensory analyses Attribute terms for sensory evaluation of cham-cham samples were developed by a nine member trained sensory evaluation panellist constituted from the faculty of Dairy Technology Division, National Dairy Research Institute, Karnal, India, using QDA methodology (Chawla et al 2014). The judges had previous experience in sensory evaluation of milk products.…”
Section: Methodsmentioning
confidence: 99%
“…QDA and PCA has been used to characterize sensorial attributes with great degree of success in many food products e.g. ultra-pasteurized milk (Chapman et al 2001), Cheddar cheese (Young et al 2004), chocolate milk (Thompson et al 2004), soy milk (Keast and Lau 2006), whey and soy proteins (Drake et al 2007), fermented food products (Ghosh and Chattopadhyay 2010), labneh (Kaaki et al 2012), yoghurt (Desai et al 2013) and doda burfi (Chawla et al 2014).…”
Section: Introductionmentioning
confidence: 99%